(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
Written corrective feedback is mainly defined as the return of information about a result of a process or an activity. And this research aims at exploring the effect of teacher’s written direct and indirect corrective feedback on the acquisition of two main grammatical structures which are tenses and subject-verb agreement, and mastering these crucial aspects in grammar will definitely lead by the end to writing and accuracy. The general focus of this study is going to be on two central types of WCF, which are direct and indirect. And according to theories of SLA and sociocultural learning, many studies assumed that the type of written corrective feedback might plays a pivotal role in helping learners recognizing their errors and correct themselves .This research will involve the use of questionnaire that follows the quantitative method design and will include students from English department from M’hamed Bougara University across all levels as participants .The data will be collected through a well-structured questionnaire over a period of ten days. The findings are expected to add insight to the pedagogical strategies applied in classes and to help students during their process of mastering the use of tenses and subject- verb agreement and might also help teachers in selecting the appropriate type of written corrective feedback.